2016
DOI: 10.3390/molecules21070863
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Profiles and Antioxidant Activity of Lotus Root Varieties

Abstract: Lotus root attracts increasing attention mainly because of its phenolic compounds known as natural antioxidants. Its thirteen varieties were systematically analyzed on the content, distribution, composition and antioxidant activity of phenolic compounds for a better understanding of this aquatic vegetable. The respective mean contents of total phenolics in their flesh, peel and nodes were 1.81, 4.30 and 7.35 mg gallic acid equivalents (GAE)/g fresh weight (FW), and those of total flavonoids were 3.35, 7.69 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
(59 reference statements)
6
30
0
Order By: Relevance
“…These results are similar to those of previous studies on J. dolomiaea [4][5][6]. The present work was consistent with reported findings which confirmed that polyphenols and flavonoids are responsible for most of the antioxidant capacity of the extracts [17][18][19][20].…”
Section: Discussionsupporting
confidence: 83%
“…These results are similar to those of previous studies on J. dolomiaea [4][5][6]. The present work was consistent with reported findings which confirmed that polyphenols and flavonoids are responsible for most of the antioxidant capacity of the extracts [17][18][19][20].…”
Section: Discussionsupporting
confidence: 83%
“…As the metabolites were the main contributor to the antioxidant and anti-inflammatory powers, the phenolic and flavonoid contents were evaluated [ 16 , 23 ]. The yield of extraction is shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It contains alkaloids that is used in treating arrhythmia, sunstroke, fever, diarrhoea, dysentery, dizziness and stomach problems (Shad et al, 2011). Furthermore, it also has pharmacological activities such as antidiarrhoeal, anti-inflammatory, antioxidant, antipyretic, diuretic, hypoglycaemic, immunomodulatory and psychopharmacological activities (Bhardwaj and Modi, 2016;Yi et al, 2016). The extract of lotus rhizome especially from its nodes contains a high amount of antioxidant such as phenolic, tannin and flavonoid (Moro, 2012).…”
Section: Introductionmentioning
confidence: 99%